Mitigating the impacts of fragmented land tenure through community-based institutional innovations: two case study villages from Guinan County of Qinghai Province, China - Gongbuzeren (Resilience Alliance, 2021)
The privatization of collectively used rangelands results in fragmentation of land use in pastoral areas. This affects pastoralists' grazing strategies and results in new institutional arrangements for addressing changing social-ecological systems. Two main systems of grazing management have emerged in the pastoral regions of the Qinghai-Tibetan Plateau that offer new perspectives on addressing rangeland fragmentation. One allows the renting of parcels of allocated grazing land to or from others (RTS) and is based on having fenced contracted parcels for each household. The other is a community-based grazing quota system (GQS) in which a grazing use quota is allocated to each household, while the community maintains collective use of the rangeland. We compare two case study villages implementing these two different management systems, operating across household and community scales, and analyze vegetation composition, above-ground biomass, and soil properties as indicators of impacts. Transects reveal that aboveground biomass was higher under the RTS than under the GQS, but species composition shifted to dominance by non-palatable forbs and graminoids. The RTS grasslands had lower carbon and nitrogen density compared to GQS-managed grasslands. These differences are consistent with the herder's perceptions of ecological changes. The general improvement of rangeland conditions under the GQS may be linked to greater herd mobility and the control of livestock numbers through the establishment of community-enforced grazing quotas. Mobility under the RTS is limited to a few parcels, and local regulation of stocking rates is minimal because the system relies on external intervention. The case of GQS suggests that addressing rangeland fragmentation with improved vegetation conditions requires institutions operating at both household and community scales allowing for mobility and regulation of stocking rates.